A proteção internacional da pessoa humana, a hospitalidade e os deslocamentos forçados por mudanças climáticas e por desastres ambientais: o por vir no Direito Internacional dos Refugiados à Luz do Direito Internacional para a Humanidade - Luciana Diniz Durães Pereira (2017)
The International Protection of the Human Being, particularly after the First and Second World Wars, has been one of the principal contemporary themes of Public International Law. Whether in its universal or regional dimension, it has developed both from the creation of a vast Human Rights regulatory framework, and through the institutionalization of bodies, mechanisms and jurisdictions exclusively geared towards the safeguarding of fundamental freedoms and rights in the international arena. In this sense, International Refugee Law is one of the fields that offers protection to human beings in situations of vulnerability and humanitarian need, and is especially intended to serve those who are victims of persecution (or who have the well-founded fear of being persecuted), and who are therefore obliged to pass through internationally recognized borders or within the territory of a nation state (internally displaced people), thereby removing themselves from their place of origin or habitual residence. This field is undergoing an epistemological crisis seeing as its main legal institute, refuge, is no longer capable of dealing with the migratory challenges currently faced by international society, above all, in the cases of forced migrations by climate change and by environmental disastres, a problem that confounds given the absence of the concept of environmental refugee. As such, and based on a humanized vision of International Law, this paper avails of the Ethics of Hospitality by the Algerian-French philosopher, Jacques Derrida, and the theorization of the Brazilian jurist, Antônio Augusto Cançado Trindade on International Law for Humankind to critically examine the future of International Refugee Law. In a world threatened by global warming and the increasing number of environmental disasters (natural or provoked by human action), it is imperative that we engage in the debate and philosophical investigation of the international legal protection to be afforded to these individuals, as well as the multilateral links of solidarity and cooperation that will bring together the subjects and players in their foreign relations, which will certainly be an essential theme on the international agenda in the coming decades.